Doxorubicin-loaded hollow gold nanospheres for dual photothermal ablation and chemoembolization therapy - Sheth, Rahul A. (Cancer Nanotechnol, 2020)
BACKGROUND: Doxorubicin-loaded hollow gold nanospheres (Dox@HAuNS) are a promising technology for simultaneous trans-arterial tumor-targeted chemotherapy delivery and thermal ablation. We evaluated the efficacy of intra-arterial delivery of Dox@HAuNS followed by photothermal ablation (PTA) in a rabbit model of liver cancer. Adult New Zealand white rabbits (N=25) were inoculated with VX2 tumors into the left lobe of the liver. The animals were then randomized to sham surgery (N=5), PTA only (N=3), Dox@HAuNS only (N=5), HAuNS + PTA (N=5), and Dox@HAuNS + PTA (N=7). Nanoparticles were delivered as an emulsion with Lipiodol (Guerbet, France) via a trans-arterial approach. Following nanoparticle delivery, PTA was performed using an 808nm fibered laser at 1.5W for 3 minutes. Thermography during PTA demonstrated a sustained elevation in tumoral temperature in both HAuNS + laser and Dox@HAuNS + laser treatment groups relative to animals that underwent laser treatment without prior nanoparticle delivery. RESULTS: There was a significant decrease in tumor volumes in all three treatment arms relative to control arms (P = 0.004). Concentrations of intratumoral doxorubicin were significantly greater in animals treated with laser compared to those that were not treated with laser (P< 0.01). CONCLUSIONS: Doxorubicin-loaded HAuNS is a promising therapeutic agent for dual ablation/chemoembolization treatment of liver cancer.